2008
DOI: 10.1016/j.exphem.2007.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Clonal predominance of CD8+ T cells in patients with unexplained neutropenia

Abstract: Objective-T-cell-mediated autoimmunity may be involved in some cases of idiopathic neutropenia. We hypothesized that a precise T-cell receptor repertoire analysis may uncover cytotoxic T-cell (CTL) expansions that are less pronounced than those seen in T large granular lymphocyte leukemia (T-LGL), but are pathophysiologically analogous and thus can serve as markers of a T-cell-mediated process. Materials and Methods-Using rational algorithms for T-cell receptor analysis and in vivotracking of CTL responses pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
0
16
0
2
Order By: Relevance
“…Wlodarski et al previously noted this overlap in the first report of the association between CPN and CD8 clonal T-cell expansions. 8 In our study, the specificity of the neutrophil antibody was identified in only 10 patients (43.5%). Detection of granulocyte-specific antibodies is highly variable and depends on studies, contexts, and methods.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Wlodarski et al previously noted this overlap in the first report of the association between CPN and CD8 clonal T-cell expansions. 8 In our study, the specificity of the neutrophil antibody was identified in only 10 patients (43.5%). Detection of granulocyte-specific antibodies is highly variable and depends on studies, contexts, and methods.…”
Section: Discussionmentioning
confidence: 94%
“…8 To better understand their clinical impact, we compared these subgroups of patients with others CPN patients of our cohort. Only 6 of the 47 patients who were tested had a T-cell clone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differentiation between leukemia and chronic LGL oligo/monoclonal lymphocytosis is sometimes impossible due to similar clinicopathological features [39]. It has been shown that neutropenia may occur in the spectrum of clonal LGL proliferations from oligoclonal to leukemia [43]. Kreutzman et al [44] showed that elevated counts of mono/oligoclonal LGLs frequently occur in chronic myeloid leukemia (CML) patients at the time of diagnosis and during imatinib therapy.…”
Section: Assessment Ofmentioning
confidence: 98%